'Getting Naked with Gok Wan': A psychoanalytic reading of How To Look Good Naked's transformational narratives. Issue 1 (1st March 2019) - Thomadaki, Theodora
Gok Wan's television fashion series How To Look Good Naked (Channel 4, 2006‐10) has vividly revolutionized the self-improvement genre. By developing a playful, caring and female-friendly makeover platform that values the articulation of emotional experiences in relation to the body, the series facilitates the exploration of the inner layers of subjectivity through the psychological exercises and self-reflective practices that Gok Wan sets out for his subjects. Playful mechanisms of creativity are central to his makeover practice, integrating fashion techniques and stylistic practices to encourage his female participants to reflect upon and make sense of their emotionally troubled experiences in relation to the body. Makeover props belonging to his female subjects play a fundamental role in activating a process of self-reflection and exploration of the self through relatedness. Through the close textual analysis of How To Look Good Naked (Series 2 Episode 6), this article applies Donald Woods Winnicott's psychoanalytic ideas (1957, 1963, 1960, 1971), to argue that the creative dimensions of Gok Wan's makeover technique reveal an object relating psychoanalytic process that entails a form of therapeutic playing; one that allows his female participants to restore aspects of self in relation to the body and to gain an emotional awareness of these experiences that leads eventually to self-discovery and self-acceptance. Ultimately, this reading of Gok Wan's method confirms the emotional and cultural value of makeover narratives to generate rich opportunities that enrich notions of inner-self experience.